Some thoughts on the Goldbach's Conjecture (Part III) - D’AMICO, Rosario (Journal of Mathematical Economics and Finance, 2019)
This work aims to formulate considerations to demonstrate the Goldbach's Conjecture by using a demonstration process by making it easier than the usual temps already present in literature.